Application of Blended Learning with Edmodo Application Based on PDEODE Learning Strategy to Increase Student Learning Achievement - Noor Emmy Ekawati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2018)
This study aims to determine the application of blended learning with edmodo application based on PDEODE learning strategy (Predict-Discuss-Explain-Observe-Discuss-Explain). The process of teaching science teaching in class VIII MTs Negeri Magelang is still running monoton that is still using conventional method, so that students are more passive. Utilization of technology and the internet is less effective, whereas facilities and infrastructure that exist in school is complete. The type of this research is Classroom Action Research (PTK) which is carried out in 4 stages, they are plan, act, observe, and reflect. Data analysis technique using gain standar to know student achievement before and after action. The results showed that the application of blended learning with edmodo application based on PDEODE learning strategy can improve student achievement of VIIIF grade MTs N Magelang. This is evidenced by the percentage of students' learning mastery of pre-cycle to cycle 1 increased 31%, increase from cycle I to cycle II by 62%, and increase from pre-cycle to cycle II by 93%.